Managing Tantrums through Storytelling: A Media Feasibility Study of a Picture Book-Based Intervention for Parents of Children Aged 3–4 Years - Menur Mustikasari; Muthmainah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study addresses the challenge faced by many parents of children aged 3–4 years who struggle to manage tantrum behaviors due to limited understanding of tantrums and appropriate handling strategies. The primary objective of this research is to develop a picture storybook that is both feasible and easy to read, aimed at supporting parents in addressing tantrum behaviors in early childhood. The study adopts a Research and Development (R&D) methodology using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—restricted to the development phase. This phase ensures the validity of the product through expert reviews and user testing. The picture storybook is designed with realistic themes that reflect tantrum-related scenarios and incorporate core values such as empathy, responsibility, and discipline. Key narrative components include characters, settings, linear plots, implicit moral messages, third-person point of view, and the use of simple language suited for early childhood contexts. Validation results show that the picture storybook was rated as highly appropriate by content experts (score: 89.5) and media experts (score: 59.5). Furthermore, parental assessment indicated the book was very easy to read, with scores of 83.8 in a small-scale test and 85.12 in a large-scale test. The results of this study imply that a well-structured picture storybook can function as an effective educational tool for improving parental understanding and strategies in managing tantrum behavior. However, a limitation of this study is the absence of data on long-term behavioral outcomes due to the restriction of the research to the development stage. Future research is recommended to employ a pretest-posttest experimental design to evaluate the book’s effectiveness in enhancing parental knowledge and attitudes. Expanding the sample size and duration of book use is also advised to assess its broader applicability.